2006
DOI: 10.1002/adma.200600001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Radiative Recombination in Silicon via Phonon Localization and Selection‐Rule Breaking

Abstract: Enhanced radiative recombination in a periodically nanoengineered silicon‐ on‐insulator structure (see figure and cover) is studied using micro‐Raman, photoluminescence, and photocurrent spectroscopies. It is shown that the enhancement is due to phonon‐ localization effects, leading to a relaxation of the fundamental k‐selection rule disfavoring light emission in bulk silicon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Si nanowires fabricated by MACE generally possess high crystalline quality, although the surface roughness of these nanowires is higher compared to VLS-grown nanowires. Compared to dry etching (e.g., RIE), chemical-based etching is considered a gentler process which tends to introduce fewer surface defects in the remaining material [16]. Recently, Oh et al reported an 18.2% cell efficiency for a MACE textured front junction device [17].…”
Section: Introductionmentioning
confidence: 99%
“…Si nanowires fabricated by MACE generally possess high crystalline quality, although the surface roughness of these nanowires is higher compared to VLS-grown nanowires. Compared to dry etching (e.g., RIE), chemical-based etching is considered a gentler process which tends to introduce fewer surface defects in the remaining material [16]. Recently, Oh et al reported an 18.2% cell efficiency for a MACE textured front junction device [17].…”
Section: Introductionmentioning
confidence: 99%
“…TEM images showing evidence of compressive strain in the pore walls are presented in ref. 28. The linewidth broadening in the C-enriched nanopatterned SOI versus the reference nanopatterned SOI is likely due to the presence of a variety of strain environments caused by C i s, C s s and other residual damage present after amorphization, C implantation, and SPE regrowth.…”
Section: Discussion : G Center Luminescence Model In Nanopatterned Simentioning
confidence: 99%
“…phonon lasers [34]. Other applications may include optical cooling [35], THz energy conversion via acoustoluminescence mechanism [36] and increasing efficiency of light emission in silicon [37]. Hypersonic phononic crystals could also have a large impact in thermal management.…”
Section: Symmetry and Phononic Band Gapsmentioning
confidence: 99%